The Impact of Protein Phosphorylation on Chlamydial Physiology - Claywell, Ja E.; Matschke, Lea M.; Fisher, Derek J. (Frontiers in Cellular and Infection Microbiology, 2016)
Chlamydia are Gram negative bacterial pathogens responsible for disease in humans and economically important domesticated animals. As obligate intracellular bacteria, they must gain entry into a host cell where they propagate within a parasitophorous organelle that serves as an interactive interface between the bacterium and the host. Nutrient acquisition, growth, and evasion of host defense mechanisms occur from this location. In addition to these cellular and bacterial dynamics, Chlamydia differentiate between two morphologically distinct forms, the elementary body and reticulate body, that are optimized for either extracellular or intracellular survival, respectively. The mechanisms regulating and mediating these diverse physiological events remain largely unknown. Reversible phosphorylation, including classical two-component signaling systems, partner switching mechanisms, and the more recently appreciated bacterial Ser/Thr/Tyr kinases and phosphatases, has gained increasing attention for its role in regulating important physiological processes in bacteria including metabolism, development, and virulence. Phosphorylation modulates these events via rapid and reversible modification of protein substrates leading to changes in enzyme activity, protein oligomerization, cell signaling, and protein localization. The characterization of several conserved chlamydial protein kinases and phosphatases along with phosphoproteome analysis suggest that Chlamydia are capable of global and growth stage-specific protein phosphorylation. This mini review will highlight the current knowledge of protein phosphorylation in Chlamydia and its potential role in chlamydial physiology and, consequently, virulence. Comparisons with other minimal genome intracellular bacterial pathogens also will be addressed with the aim of illustrating the importance of this understudied regulatory mechanism on pathogenesis and the principle questions that remain unanswered.